2017
DOI: 10.1021/acssuschemeng.7b01448
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Colorimetric Assay of H2S Depending on the High-Efficient Inhibition of Catalytic Performance of Ru Nanoparticles

Abstract: Nanocatalysts depended colorimetric assay possesses the advantage of fast detection and provides a novel avenue for the detection of hydrogen sulfide (H2S). The exploration of nanocatalysts with superior catalytic activity is challenging to achieve ultrasensitive colorimetric assay of H2S. Herein, 1.7 ± 0.2 nm ruthenium nanoparticles (Ru NPs) were prepared and exhibited outstanding catalytic hydrogenation activity. The degradation rate constants of orange I in the presence of Ru NPs were 4-, 47- and 165-fold h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Its removal is required in industrial processes as a result of pollution control and human health concerns. 1,2 Currently, the widely used technology for H 2 S elimination is a multistep Claus process. 3 However, due to the thermodynamic limitations, there is around 4% H 2 S left after undergoing the process.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Its removal is required in industrial processes as a result of pollution control and human health concerns. 1,2 Currently, the widely used technology for H 2 S elimination is a multistep Claus process. 3 However, due to the thermodynamic limitations, there is around 4% H 2 S left after undergoing the process.…”
Section: ■ Introductionmentioning
confidence: 97%
“…H 2 S is corrosive, malodorous, and highly toxic. Its removal is required in industrial processes as a result of pollution control and human health concerns. , Currently, the widely used technology for H 2 S elimination is a multistep Claus process . However, due to the thermodynamic limitations, there is around 4% H 2 S left after undergoing the process. With the increasingly stringent regulations on the emission of sulfur compounds, various desulfurization processes were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is the third endogenous gas in mammals which has a great influence on human physiology and pathology including neurotransmission, vasodilation, and regulation of gastrointestinal and liver functions. Notably, it has been reported that the average concentration of endogenous H 2 S is in the mM range, but due to the rapid synthesis and catabolism of intracellular H 2 S, the concentration of endogenous H 2 S can vary from sub-mM to a few nM rapidly . Therefore, it is highly desirable to develop a reliable and highly sensitive assay to monitor and track H 2 S in living cells or biological samples.…”
Section: Introductionmentioning
confidence: 64%
“…As demonstrated in Figure b, in the presence of 100 nM Na 2 S, RuCu cage NPs showed a significantly decreased electro-oxidation peak at 0.84 V, while the oxidation signal at −0.16 V was very weak and no change was observed. However, RuCu alloy NPs only showed negligible DPV peak changes at both 0.84 and −0.16 V. Compared with RuCu alloy NPs, RuCu cage NPs showed a more sensitive response toward Na 2 S and became an alternative electroactive tag for the detection of Na 2 S. This was due to the main presence of Ru 0 in RuCu cage NPs and the unique hollow structure for the exposure of more Ru 0 electroactive sites for the rapid reaction with Na 2 S. The presence of Na 2 S induced the formation of the Ru–S bond, leading to the formation of Ru x S y components and decreasing the DPV signal of Ru 0 at 0.84 V. The DPV responses of RuCu cage NPs showed no obvious changes in the presence of 100 nM Na 2 S at different pH values ranging from 6 to 9, indicating the good stability of RuCu cage NPs for the application of Na 2 S detection (Figure S7). RuCu cage NPs with strong DPV peak at 0.84 V became an alternative electroactive tag for the detection of Na 2 S.…”
Section: Resultsmentioning
confidence: 99%